Several Different Types of Convergence for ND Random Variables under Sublinear Expectations - Ziwei Liang; Qunying Wu (Discrete Dynamics in Nature and Society, 2021)
The goal of this paper is to build average convergence and almost sure convergence for ND (negatively dependent) sequences of random variables under sublinear expectation space. By using the basic definition of sublinear expectation space, Markov inequality, and Cr inequality, we extend average convergence and almost sure convergence theorems for ND sequences of random variables under sublinear expectation space, and we provide a way to learn this subject.